2008
DOI: 10.1016/j.mcn.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Sema3A signal with a L1 mimetic peptide is not sufficient to promote motor recovery and axon regeneration after spinal cord injury

Abstract: We examined whether Sema3A which is upregulated at the site of spinal cord injury exerts a direct effect on axons. We used ASNKL peptide that prevents specifically the inhibitory effect of Sema3A on L1/Neuropilin1 (Nrp1) expressing axons. In the naïve mouse spinal cord, L1 is located on a subset of corticospinal axons, whereas Nrp1 is barely detectable. After contusion injury, Nrp1 is found on L1-negative immune cells whereas its expression does not increase on severed axons. L1 expressing axons sprout extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…For the analysis of axon length, the NeuronJ plugin of ImageJ software was used, as previously described [29]. Briefly, the length of a maximum of 40 axons (mean 24.1 ± 1.5 axons) for both normal and underfed was measured for each explants.…”
Section: Methodsmentioning
confidence: 99%
“…For the analysis of axon length, the NeuronJ plugin of ImageJ software was used, as previously described [29]. Briefly, the length of a maximum of 40 axons (mean 24.1 ± 1.5 axons) for both normal and underfed was measured for each explants.…”
Section: Methodsmentioning
confidence: 99%
“…The following groups were assigned: vehicle + spinal cord injury (SCI), TGF-α + SCI, vehicle + laminectomy, TGF-α + laminectomy. Prior studies have shown that the catheter placement in mice results in a local inflammatory response and a transient behavioral impairment, but has no long-term effects on behavioral recovery compared with animals with no catheter (Mire et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Cultured pyramidal neurons isolated from embryonic hippocampus transfected with the HyPer biosensor were treated in situ with a Sema3A-conditioned medium (300 μg/ml, 20 nM) to promote complete growth cone collapse (N 85%) (Antipenko et al, 2003;Mire et al, 2008). H 2 O 2 production was measured in the same neuron every 30 s during 15 min.…”
Section: Treatment With Wild-type Recombinant Gal-1 Decreases Neuronamentioning
confidence: 99%